Spatial Distribution of Total Petroleum Hydrocarbon (TPH) in Sediment of Sumba Sea, Nusa Tenggara Timur - Yogaswara, Deny; Khozanah, Khozanah (Oseanologi dan Limnologi di Indonesia, 2018)
Sumba Sea is an Indo-Australian tectonic plate transition zone that has a huge biodiversities resources and also behalf of an international shipping lane zone from southern of Indonesia to Australia and New Zealand, and as the return. In addition, Sumba Sea is also a kind of outer boundary of Indonesia, that is necessary to do basic environmental monitoring as the authorities in the management of outer sea zone. Indonesia does not have representative environmental quality database including the pollution of Total Petroleum Hydrocarbons (TPH). This study purposes to determine the partial distribution and concentration of TPH in sediments in Sumba Sea, East Nusa Tenggara. The research was conducted in August 2016 using Research Vessel of Baruna Jaya VIII. Samples were collected using a box core, preserved in amber glass jar bottle and stored at 4Â°C for further analysis in the laboratory. In the laboratory, sediment samples were extracted using dichloromethane and n-hexane for three times extraction. Furthermore, samples were evaporated before added by tetrachloroethylene solvent. Samples were measured with Fourier Transform Infra Red (FTIR) at wavelength 2850-2950 cm-1. The results showed that the pollution of Total Petroleum Hydrocarbon (TPH) in the Sumba Sea was detected at all sampling station based on identified of hydrocarbon functional groups. The partial distribution of TPH is evenly distributed and covered all stations on low concentrations. The highest concentration of TPH was detected at station 10 as 4.348 ppm